2018
DOI: 10.1002/acn3.633
|View full text |Cite
|
Sign up to set email alerts
|

Effect of smoking cessation on the risk of dementia: a longitudinal study

Abstract: ObjectiveTo determine the risk of developing dementia in relation to duration of smoking cessation by using a nationwide health claims database.MethodsThis cohort study included 46,140 men aged 60 years or older from Korean National Health Insurance System – National Health Screening Cohort, a population‐based national health screening program from 2002 to 2013. The changes in smoking habit from a questionnaire during the first (2002 and 2003) and second (2004 and 2005) health examination periods, participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
73
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(83 citation statements)
references
References 51 publications
(56 reference statements)
2
73
1
Order By: Relevance
“…Many factors that increase the risk of cardiovascular disease are also associated with a higher risk of dementia. 88 These factors include smoking [89][90][91][92][93] and diabetes. [94][95][96][97] Some studies propose that impaired glucose processing (a precursor to diabetes) may also result in an increased risk for dementia.…”
Section: Cardiovascular Disease Risk Factorsmentioning
confidence: 99%
“…Many factors that increase the risk of cardiovascular disease are also associated with a higher risk of dementia. 88 These factors include smoking [89][90][91][92][93] and diabetes. [94][95][96][97] Some studies propose that impaired glucose processing (a precursor to diabetes) may also result in an increased risk for dementia.…”
Section: Cardiovascular Disease Risk Factorsmentioning
confidence: 99%
“…Surprisingly, no strong evidence supporting a connection between passive smoking and an increased risk of dementia has been yet found [ 118 ]. On the other hand, the risk of dementia is reduced once an individual quits smoking for a prolonged time, therefore, it is of great importance to public health to help smokers quit smoking [ 119 ].…”
Section: Other Established (Non-)modifiable Risk Factors and Possimentioning
confidence: 99%
“…However, it is still uncertain how long a period of smoking cessation would begin to reduce the risk of dementia. One study has compared the risk of all-cause dementia, Alzheimer's disease (AD), and vascular dementia (VaD) between current smokers and ex-smokers, and found that the risk decreased in those who had quit for 4 years or longer [20].…”
Section: Introductionmentioning
confidence: 99%